IN SILICO ANALYSIS OF FIG (Ficus carica L.) BIOACTIVE COMPOUNDS AS MULTITARGET THERAPEUTIC CANDIDATE AGAINST HIV-1 - Musa'adah Musa'adah; Ayuni Adawiyah; Raysha Tryfhatya Nurhaidha; Yani Suryani; Risda Arba Ulfa (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Antiretroviral drugs (ARV) to treat HIV-1 infection which causes AIDS are predominantly monotargeted so it is considered less effective. Long-term use of this drug may also lead to side effects and the HIV-1 resistance to drug. Thereby highlighting the need for developing more effective multitarget drug candidates. Herbal-based medicine have potential to be developed into multitarget drugs due to its diverse bioactive compounds. In silico approaches are used for initial screening in new drug development. This study aimed to evaluate the potential of fig (Ficus carica L.)-derived bioactive compounds as multitarget antiretroviral therapy candidates against three key HIV-1 proteins: Gp120, HIV-1 reverse transcriptase, and HIV-1 protease, in silico. Fourteen bioactive compounds consisting of anthocyanin, flavonoid, and terpenoid derivatives were analyzed for their physicochemical properties, pharmacokinetic profiles, toxicity, and molecular docking interactions. The results revealed that five compounds of flavonoid group: apigenin, catechin, epicatechin, kaempferol, and luteolin, fulfilled the criteria as potential oral multitarget drug candidates with relatively low binding affinity (ΔG) values toward all three HIV-1 target proteins. Notably, luteolin exhibited the strongest binding affinity toward Gp120 (-7.2 kcal/mol), HIV-1 reverse transcriptase (-8.8 kcal/mol) and HIV-1 protease (-8.5 kcal/mol), while also complying Lipinski’s, ADMET parameters, and low-toxicity predictions. These findings suggest that luteolin considerable as a safe natural-based multitarget antiretroviral candidate derived from Ficus carica L.